Angiopoietin-1 induces survival and proliferation of hair follicle dermal papilla cells through integrin α5β1 signaling - Yun, Jang-Hyuk (Frontiers in Medicine, 2025)
BackgroundAndrogenetic alopecia is a common form of hair loss primarily mediated by dihydrotestosterone (DHT), which induces apoptosis and inhibits proliferation in dermal papilla cells (DPCs). Current treatments, such as minoxidil and finasteride, often show limited efficacy and can cause adverse effects, underscoring the need for safer and more targeted therapies.MethodsThis study investigated the protective and proliferative effects of angiopoietin-1 (Ang1) on human follicle dermal papilla cells (HFDPCs) under DHT-induced stress. Apoptosis and proliferation were assessed using flow cytometry and BrdU assays. Western blotting was used to examine intracellular signaling pathways. The expression and functional relevance of Tie and integrin receptors were evaluated using gene expression analysis and blocking antibodies.ResultsAng1 significantly reduced DHT-induced apoptosis and restored proliferation in HFDPCs. These effects were mediated via activation of the PI3K/AKT and MAPK/ERK1/2 pathways through integrin α5β1. Neither Tie-1 nor Tie-2 receptors were detected in HFDPCs, indicating that Ang1 acts through a Tie-2-independent mechanism. Given the well-established role of Ang1 in promoting vascular stability via the Tie-1–Tie-2 axis in endothelial cells, it is plausible that Ang1 may also support follicular health indirectly by enhancing perifollicular vascularization.ConclusionAng1 enhances HFDPC survival and proliferation through integrin α5β1-mediated signaling. In addition to its direct protective effects on DPCs, Ang1 may promote angiogenic support in the hair follicle microenvironment. These findings position Ang1 as a potential dual-action therapeutic candidate for androgenetic alopecia.